Apathy in Lewy body disease and its effects on functional impairment over time - Zhu, Carolyn W.; Grossman, Hillel T.; Elder, Gregory A.; Rosen, Howie; Sano, Mary (Frontiers in Neurology, 2024)
Background and objectives Apathy strongly affects function in Alzheimer’s disease and frontotemporal dementia, however its effect on function in Lewy Body Disease (LBD) has not been well-described. This study aims to (1) examine the prevalence and persistence of apathy in a large, national cohort of well-characterized patients with LBD, and (2) estimate the effect of apathy on function over time. Methods Study included 676 participants with mild cognitive impairment (MCI) or dementia in the National Alzheimer’s Coordinating Center Uniform Data Set. Participants were followed for an average of 3.4 ± 1.7 years and consistently had a primary diagnosis of LBD. Apathy was defined by clinician judgment, categorized into four mutually exclusive profiles: (1) never apathetic across all visits, (2) at least one but <50% of visits with apathy (intermittent apathy), (3) ≥50% but not all visits with apathy (persistent apathy), and (4) always apathy across all visits. Dementia severity was measured by baseline Clinical Dementia Rating score. Parkinsonism was defined by the presence of bradykinesia, resting tremor, rigidity, gait, and postural instability. Functional impairment was assessed using the Functional Assessment Questionnaire (FAQ). Results Baseline characteristics of the sample were: average age = 72.9 ± 6.9, years of education = 15.6 ± 3.4, Mini Mental State Exam (MMSE) = 24.4 ± 5.4, Geriatric Depression Scale (GDS) = 3.8 ± 3.2, FAQ = 12.0 ± 9.1. 78.8% were male and 89% were non-Hispanic white. Prevalence of apathy increased from 54.4% at baseline to 65.5% in year 4. 77% of participants had apathy at some point during follow-up. Independent of cognitive status and parkinsonian features, FAQ was significantly higher in participants with intermittent/persistent and always apathetic than never apathetic. Annual rate of decline in FAQ was faster in participants who were always apathetic than never apathy. Discussion In this large national longitudinal cohort of LBD patients with cognitive impairment, apathy was strongly associated with greater functional impairment at baseline and faster rate of decline over time. The magnitude of these effects were clinically important and were observed beyond the effects on function from participants’ cognitive status and parkinsonism, highlighting the importance of specifically assessing for apathy in LBD.